The Demand for Money and Economic Uncertainty - Lim, Siew Yong; Gan, Pei Tha (International Business Education Journal, 2015)
A well organize monetary policy depends on a stable demand for money. Therefore, the stability of the money demand function is a necessary condition for ensuring implementation and application of central bank’s monetary policy. The aim of this paper is to propose an investigation framework on the relationship between the money demand and the economic uncertainty. This study extends the Keynes’s money demand function by including the optimal economic uncertainty index that proposed by Gan (2014). The expected finding suggests that the optimal economic uncertainty fulfils its role as a useful uncertainty indicator for central bank’s monetary policy procedure, which may help to improve the knowledge concerning the demand for money and improve the correctness of money demand theory. The expected finding also suggest that the optimal economic uncertainty index can serve as a predictive content for money demand, and therefore, the monetary targeting can serve as an important monetary policy strategy as the uncertainty inherent in the money demand can be identified by using the optimal economic uncertainty index.